AGENDA 5.0: CITIZEN JOURNALISM IN SHAPING THE AGENDA - Oksana Pochapska (Інтегровані комунікації)
Modern society, immersed in information flows, is increasingly faced with the phenomenon of information overload. In such conditions, data perception occurs mainly fragmentarily and at two levels - conscious and unconscious- when a significant part of the information is absorbed in the form of so-called information noise. A critical element of technology that attracts or distracts attention is the activities of citizen journalists, who act as opinion leaders for certain audiences of social media users. Their ability to quickly disseminate information from public perceptions about the "mass support" of individual ideas or positions makes them a powerful tool for influencing public opinion. Using the publications of citizen journalists as a source of news, creating the necessary information background, and initiating or supporting specific topics is only part of the manipulative potential of modern citizen journalism, which actively functions in ecosystems of social networks, blogs, and messengers.